Effect of Polypropylene Fibers on Swelling Potential and Shear Strength of Clay - Daksi M. Yacine; Sid Madani; Mehdi Dib (Civil Engineering Journal, 2023)
Expansive clays can cause major problems for urban development (roads, railways, infrastructure, etc.); therefore, reducing the swelling potential of clays has always been a concern in the geotechnical field. The presented paper investigates the effect of polypropylene reinforcement fibers on the swelling potential and shear strength of clay. The samples studied were taken from the clayey region of Mila, located in the northern east of Algeria. The experimental procedure adopted in this research consists first of the assessment of the physical, mechanical, and mineralogical characteristics of the soil samples without reinforcement. Then, swelling pressure, swelling rate, and swelling index are used to assess the swelling potential of these samples. After the reinforcement using a variety of polypropylene fiber concentrations (2 to 6% of the weight of the dry clay), the free swelling is clearly reduced. The optimum reinforcement rate in this case is 4%, in which the swelling was reduced by 90.7%. Finally, to offer more insights regarding the impact of clay reinforcement using polypropylene fibers, the effect of this later on the mechanical properties of the studied clay was also analyzed through the tangential shear strength. It was found that the polypropylene fibers increased the tangential shear resistance of Mila’s clay. Doi: 10.28991/CEJ-2023-09-03-04 Full Text: PDF